STUDENTS' PERCEPTION ON THE TEACHERS' USE OF ENGLISH AT AN EFL CONTEXT: a Case Study at One State Senior High School in Yogyakarta - Zeni, Mohamad (2009)
This research attempts to portray the possibility of using English actively in EFL classroom by the English teachers especially in public and private senior high schools in Indonesia. This study was conducted to reveal the first research question: students' perception on the teachers' Use of English in EFL classroom and the second research question: how the teachers' use of English influences classroom interaction. This research was conducted in one public senior high school in Yogyakarta involving 100 eleventh grade students from four classes using purposive sampling in qualitative case study. The data were collected through questionnaire, students' interview and classroom observation. From the elements (variables) influencing someone's perception, the theory of perception by Sperling (1987) the researcher develop the questionnaire and interview to answer the first research questions about students' positive and negative perception on the teachers' use of English. The students' response from the questionnaire were tabulated into percentage then interpreted to explore the first research question of this study. In this study, the data from students' interview and classroom observation was transcribed and analyzed and synthesized to answer the second research question about positive and negative influence of using English actively in EFL classroom by English teachers in a state senior high school in Yogyakarta. The result from questionnaire showed that 95 out of 100 (95% respondents) had positive perception towards the teachers' use of English. The interview showed that the students were happy with active teachers' use of English in EFL classroom in Senior High School. During EFL classroom activities the teachers gave so much English exposure in the class. From the questionnaire, only 5% of the respondents negatively responded the teachers' use of English in the class. From that percentage, the researcher got the data revealing that 90% stated that their present English teachers used English actively, 88% respondents were happy, 95% were encouraged, 95 were enthusiastic, with their active teachers' use of English. 97% stated that their aims of learning English were facilitated by their active teachers' use of English. About their teachers' use of English at their junior high school, they agreed (85%) with their active teachers' use of English. From their experience of having active teachers' of English in EFL classroom, most students gained personal goals at the level of: problem solving (99%), group work (94%). increasing interactive learning with friends (92%) self confidence (90%), %), and critical thinking skill (87%) The data from classroom observation transcript and interview were integrated to explore influence of teachers' use of English to classroom interaction. From the data of both instruments, it revealed that most students showed that most students were active, enjoying, having good emotion, respect to the teachers, and self confident when the teachers used English actively in the class. Hopefully, these findings of this research would be a great help for senior high school English teachers in making decision on whether they should use English or Indonesian during teaching learning process in classroom. Further more, this research can give enlightening, valuable information, especially for English teachers to improve the students' communicative competence in English. In addition, this research might also inspire other researchers to conduct research on issues concerning with the same field due to that this research was not to generalize the other population.